On the compositional and structural redistribution during partial recrystallisation: a case of σ-phase precipitation in a Mo-doped NiCoCr medium-entropy alloy. (15th March 2021) - He, Junyang; Wu, Xiaoxiang; Guo, Yueling; Makineni, Surendra Kumar
Abstract: In this work, we discussed the atomic-scale mass transport occurring in a Mo-doped NiCoCr medium-entropy alloy to form σ-precipitates during partial recrystallization at 700°C. We reveal the segregation of Cr/Mo to the fault planes of nano-twins/stacking faults in non-recrystallized zones. Upon annealing, the migration of recrystallized grain boundaries (GBs) redistributes the structure and composition, leading to the annihilation of faults and leaving behind the Mo-rich σ-precursors for precipitation. The segregated Cr/Mo solutes can also diffuse to the moving GBs and create additional σ-nucleation sites. The present results highlight the role of Mo in overcoming strength-ductility trade-off of the alloy. Graphical Abstract: Image, graphical abstract